2011
DOI: 10.1101/gr.113555.110
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive long-span paired-end-tag mapping reveals characteristic patterns of structural variations in epithelial cancer genomes

Abstract: Somatic genome rearrangements are thought to play important roles in cancer development. We optimized a long-span paired-end-tag (PET) sequencing approach using 10-Kb genomic DNA inserts to study human genome structural variations (SVs). The use of a 10-Kb insert size allows the identification of breakpoints within repetitive or homology-containing regions of a few kilobases in size and results in a higher physical coverage compared with small insert libraries with the same sequencing effort. We have applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 32 publications
2
104
0
Order By: Relevance
“…This first characterization of NPC by deep whole genome sequencing demonstrated effective structural variant discovery with our approach, which involved (1) generation of high-complexity, long-insert mate-pair libraries by a novel combination of methods; (Williams et al 2012) and tumor genomes (Hillmer et al 2011), our study achieves the deepest-to date-physical coverage (7503) as well as high sequence coverage (583) with a single mate-pair library. The great degree of physical coverage afforded by long-insert mate-pair libraries facilitated our proof-of-concept demonstration that structural variants can be discovered even in very low-tumor content samples: In the case of NPC-5421, two of three gene fusion variants were inferred from the mate pair data to be present at only 6% allele frequency; both were validated by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This first characterization of NPC by deep whole genome sequencing demonstrated effective structural variant discovery with our approach, which involved (1) generation of high-complexity, long-insert mate-pair libraries by a novel combination of methods; (Williams et al 2012) and tumor genomes (Hillmer et al 2011), our study achieves the deepest-to date-physical coverage (7503) as well as high sequence coverage (583) with a single mate-pair library. The great degree of physical coverage afforded by long-insert mate-pair libraries facilitated our proof-of-concept demonstration that structural variants can be discovered even in very low-tumor content samples: In the case of NPC-5421, two of three gene fusion variants were inferred from the mate pair data to be present at only 6% allele frequency; both were validated by Sanger sequencing.…”
Section: Discussionmentioning
confidence: 94%
“…For technical reasons, it is difficult to obtain deep genome coverage with inserts exceeding 600 bp using this approach. Much larger inserts can be produced by circularizing large DNA fragments of up to 10 kb (Fullwood et al 2009;Hillmer et al 2011), and subsequent isolation of a short fragment that contains both ends (mate pairs). Large-insert and fosmid mate-pair libraries offer several attractive features that make them well-suited for analysis of structural variation (Raphael et al 2003;International Human Genome Sequencing Consortium 2004;Tuzun et al 2005;Kidd et al 2008;Hampton et al 2011;Williams et al 2012).…”
mentioning
confidence: 99%
“…A catalog of somatic structural variation data was compiled from a number of WGS studies, comprising a total of 277 tumor samples, as listed in Dataset S1 (4,9,10,(15)(16)(17)(18)(19)(20)(21)(22). We manually curated the available structural variation information (relative orientation and mapping coordinates of the discordant mate-pair or paired-end read clusters) from every individual study to classify each reported somatic event into one of the four basic rearrangements: deletion, TD, inversion, or interchromosomal translocation (49).…”
Section: Methodsmentioning
confidence: 99%
“…Previous attempts at describing the genomic features of the TDP have relied on a basic TD count or on the proportion of TDs relative to the total number of structural variations in a cancer genome (10,15). These approaches lack in robustness, because they are prone to be influenced by observer and technical biases, such as sequencing coverage, and are not able to discriminate between the genome-wide TD prevalence that characterizes the TDP vs. abnormal TD accumulation in a few functional genomic loci, previously described in association with focal amplification (9,16). Our proposed metric to calculate the TDP score is described in the main text.…”
Section: Methodsmentioning
confidence: 99%
“…In our experiments, we used an insert size of 3 kb, which provides a good balance between resolution and the ability to detect breakpoints across repetitive regions. 14,30 We estimated the resolution that can be reached based on clustering analysis by calculating the distribution of the sizes of deletions predicted by our analysis (Supplementary Figure S5). This shows that the majority of deletions is smaller than 10 kb and the lower detection limit is B1 kb.…”
Section: Resultsmentioning
confidence: 99%